Medical Honey for Wound Care—Still the 'Latest Resort'?. Issue 2 (2009) - Simon, Arne; Traynor, Kirsten; Santos, Kai; Blaser, Gisela; Bode, Udo; Molan, Peter
Abstract : While the ancient Egyptians and Greeks used honey for wound care, and a broad spectrum of wounds are treated all over the world with natural unprocessed honeys from different sources, Medihoney™ has been one of the first medically certified honeys licensed as a medical product for professional wound care in Europe and Australia. Our experience with medical honey in wound care refers only to this product. In this review, we put our clinical experience into a broader perspective to comment on the use of medical honey in wound care. More prospective randomized studies on a wider range of types of wounds are needed to confirm the safety and efficacy of medical honey in wound care. Nonetheless, the current evidence confirming the antibacterial properties and additional beneficial effects of medical honey on wound healing should encourage other wound care professionals to use CE-certified honey dressings with standardized antibacterial activity, such as Medihoney™ products, as an alternative treatment approach in wounds of different natures.